2016
DOI: 10.1002/bit.26076
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rhodobacter capsulatus self‐reporting model system for optimizing light‐dependent, [FeFe]‐hydrogenase‐driven H2 production

Abstract: The photosynthetic bacterium Rhodobacter capsulatus normally photoproduces H as a by-product of its nitrogenase-catalyzed nitrogen-fixing activity. Such H production, however, is expensive from a metabolic perspective, requiring nearly four times as many photons as the equivalent algal hydrogenase-based system (Ghirardi et al., 2009 Photobiological hydrogen-producing systems. Chem Soc Rev 38(1):52-61). Here, we report the insertion of a Clostridium acetobutylicum [FeFe]-hydrogenase and its three attendant hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…We successfully implemented two parts of the four-part H 2 -responsive signal transduction cascade from C. necator in the cyanobacterium Synechocystis. This is considered as a first step toward a synthetic cyanobacterial H 2 biosensor that could be used analogously to previous reports (Wecker et al, 2017). A potential application would be, for instance, to optimize the H 2 evolution activities of heterologously produced O 2 -tolerant, energy-converting hydrogenases, one of which was successfully implemented in Synechocystis recently (Lupacchini et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We successfully implemented two parts of the four-part H 2 -responsive signal transduction cascade from C. necator in the cyanobacterium Synechocystis. This is considered as a first step toward a synthetic cyanobacterial H 2 biosensor that could be used analogously to previous reports (Wecker et al, 2017). A potential application would be, for instance, to optimize the H 2 evolution activities of heterologously produced O 2 -tolerant, energy-converting hydrogenases, one of which was successfully implemented in Synechocystis recently (Lupacchini et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…For example, Wecker et al used engineered R. capsulatus strains that monitor H 2 by reporter fluorescence to track the activity of a recombinant H 2 -evolving hydrogenase from Clostridium acetobutylicum . Only low H 2 production has been detected, but the system potentially enables further screening and hydrogenase evolution approaches ( Wecker et al, 2017 ). We successfully implemented two parts of the four-part H 2 -responsive signal transduction cascade from C. necator in the cyanobacterium Synechocystis .…”
Section: Discussionmentioning
confidence: 99%
“…Wecker et al. [90] reported hup ‐based bioH 2 production by R. capsulatus cells. This strain was initially deprived of native uptake hydrogenase.…”
Section: Methods For Enhancement Of Pfhpmentioning
confidence: 99%
“…Elimination of hup from the genome of R. sphaeroides cells enhanced bioH 2 production rates by 11-40% as compared to the wild strain. Wecker et al [90] reported hup-based bioH 2 production by R. capsulatus cells. This strain was initially deprived of native uptake hydrogenase.…”
Section: Inactivation Of Uptake Hydrogenasementioning
confidence: 99%